America street : a multicultural anthology of stories - Mazer, Anne. (New York : Persea Books, 1993)
Fourteen stories by American authors from diverse racial and cultural backgrounds, including Duane Big Eagle, Nicholasa Mohr, Lensey Namioka, and Robert Cormier.
The journey / Duane Big Eagle -- Raymond's run / Toni Cade Bambara -- The circuit / Francisco Jimenez -- The wrong lunch line / Nicholasa Mohr -- The loudest voice / Grace Paley -- Thank you m'am / Langston Hughes -- The all-American slurp / Lensey Namioka -- The no-guitar blues / Gary Soto -- Sixth grade / Michele Wallace -- President Cleveland, where are you / Robert Cormier -- Business at eleven / Toshio Mori -- La ciramella / Mary K. Mazotti -- The white umbrella / Gish Jen -- Hamadi / Naomi Shihab Nye
Keywords: Children's stories, American; Short stories